Entrepreneurial Climate in India, China and the USA - S, Mahalakshmi; S, Thiyagarajan; Sodhi, Ranbir; G, Naresh (Organizations and Markets in Emerging Economies, 2023)
Entrepreneurship plays a vital role in the process of wealth creation and improving the standard of living of the people through large-scale employment generation. So this study aims to identify the critical factors among the entrepreneurial framework conditions (EFC) and entrepreneurial behaviour and attitudes (EBAA) in enhancing the entrepreneurship climate in the United States of America (USA), China and India. The data for the study is collected from GEM (Global Entrepreneurship Monitor) on EBAA and EFC. Exploratory factor analysis was attempted initially to reduce the EBAA and EFC data into manageable factors. Further, confirmatory factor analysis was attempted to cross-validate the results. Key Points: • The results unveil that the Public conditions and Business Promotions (EFC) in the USA are superior to India and China. At the same time, India lags behind both the USA and China. • Indian entrepreneurs are more optimistic and audacious than their Chinese counterparts. • The future of entrepreneurship in India depends on what measures the Government adopts today to strengthen the entrepreneurship framework conditions.